The Use of Bilingualism Strategy as a Communication Tool in English Learning - Pauziyah, Rosmalinda; Zifafiyyah, Lailatuz (Universitas Siliwangi, 2024)
One of the difficulties faced by English teachers is how to make English acceptable, understood, and well-controlled by their students. One of the strategies to use is bilingualism or using both students’ first and target languages in the classroom. This research aims to investigate the types of bilingualism in the vocabulary mix used in Indonesian English classes and explore the functions of bilingualism in the English learning process. This research was conducted by a descriptive qualitative. To collect the data, this research employed content analysis. Meanwhile, to analyse the data this study employed the theory of Lasswell’s idea: quantification of the word domain (types of bilingualism in vocabulary mix). Based on this research, it has been found that there are three types of bilingualism in the English learning process in Indonesia with a vocabulary mix of Indonesian vocabulary and English vocabulary, they are compound bilingualism, coordinate bilingualism and subordinate bilingualism. Its functions in the English learning process are to provide opportunities for students to speak English with each other, the learning process feels fun, and students are easier to understand the material. In addition, another phenomenon was found, namely the most used type of bilingualism is coordinate bilingualism. The benefits of the result are information as well as references to support teaching and learning activities using bilingualism in English class learning. Keywords: Bilingualism; communication tools; English learning.